Analysis of the Use of GPT Chat to Improve Student Performance - Jumriah, Jumriah; Susilawati, Eneng Sri; Supriatna, Eka; Smas, Musa Hefer; Arini, Ira (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
An AI-powered system that enables text-based conversational interactions, the Generative Pre-training Transformer (GPT). GPT has various functions, including language translation, providing recommendations, increasing productivity, and assisting in education. The benefits of using GPT in education include personalized learning, accessibility, interactive learning resources, and assistance with assignments and problem solving. However, there are limitations to using GPT Chat, such as its limited understanding, inability to replace creative work, and its tendency to provide inaccurate answers. Additionally, it cannot differentiate between fact and opinion, and requires a stable internet connection. While Chat GPT can be useful for instant data retrieval, summaries, and other research tasks, it should not be relied upon as a replacement for manual research processes. Continuing ongoing research and development is crucial to maximize the benefits of using Chat GPT while overcoming existing challenges.